Gambaran Niat Masyarakat dalam Menerapkan Protokol Kesehatan pada Pasar Tradisional selama Masa Pandemi di Kota Surabaya - Hakim, Dzakwan Rakha; Salim, Lutfi Agus; Mardhani, Mochamad Azhari (Universitas Airlangga, 2024)
Background: A place that needs to be watched out for as a place that can cause the COVID-19 virus is traditional markets, because traditional markets are meeting places for many people. Traditional markets can later have a positive impact on breaking the chain of transmission of COVID-19 through health protocol policies. Theory of Planned Behavior provides an explanation that there are three factors that influence an individual's intentions, namely controlling behavior, attitudes, and subjective norms. Objectives: From this research activity the aim is to carry out an analysis regarding the depiction of a person's intentions in implementing health protocols in traditional markets during the COVID-19 pandemic in Surabaya. Methods: The research technique or method used is quantitative research with a descriptive observational research design using a cross-sectional design. Results: From the research activities that have been carried out, the results state that the majority of respondents are aged 19 to 30 years and have the last education of SMA or SMK equivalent. The majority of respondents also have good knowledge and have very good control over behavior, attitudes, and subjective norms. Not only that, but the majority of respondents also have the power of intention in implementing health protocols in traditional markets. Conclusions: From the research activities that have been carried out, a conclusion can be drawn that the majority of respondents have strong intentions to implement health protocols in traditional markets. Controlling the behavior of attitudes and subjective norms of the majority of respondents in the very good category which is a factor influencing their intentions. Not only that, this was also driven by respondents whose characteristics were in their productive age and had good knowledge and education. With that, respondents are expected to be able to make the application of health protocols in these traditional markets a habit that is needed to be implemented in their daily lives.